Increasing the performance of the Far Eastern Railway traction power supply system - N. P. Grigor’ev; I. V. Ignatenko; S. A. Vlasenko; V. A. Kovalev; V. V. Shatalov (Вестник Научно-исследовательского института железнодорожного транспорта, 2022)
Introduction. The purpose of the study is to develop measures determined by the strategic programmes for the development of Russian railway transport based on the analysis of power supply schemes for the traction network of the Far Eastern Railway, a branch of Russian Railways.Materials and methods. Evaluation of the performance of the traction power supply system was made based on the analysis of the actual performance of the Far Eastern Railway section, as well as the theories of electrical engineering and power supply of the 25 kV AC electrified railway system.Results. Based on the analysis of the joint operation of the external and traction power supply systems of the Far Eastern Railway, four traction substations with low technical and economic indicators were identified. Network sections that feed the substations are a bottleneck in the traction power supply system. It is proposed to increase the efficiency by switching the connection of the windings of transformers of traction substations to the systems of external and traction power supply according to the typical star – delta scheme. Such a connection will ensure an increase in the speed of trains, a reduction in train succession time and losses of electricity, an increase in the quality of electric energy in the external power supply system and electric networks of the Far Eastern Directorate for Energy Supply (a structural subdivision of Transenergo, a branch of Russian Railways).Discussion and conclusion. Normalisation of the connection of four traction substations according to the feeding scheme is ensured by changing the phasing in such a way that the power supply of the two legs of one winding of the power transformer is transferred to two windings. Alignment of the current modules in the windings of transformers of traction substations makes it possible to reduce the voltage drop in the most loaded phase and, accordingly, increase the voltage in the traction network, which ensures an increase in the speed of trains and a reduction in passing intervals. Switching the power supply of the arms from one winding of the transformer to two reduces the loss of electrical energy in power transformers and the external power supply system. Reducing the current unbalance in the windings of the power transformer improves the quality of electrical energy in the system of external and district power supply. An increase in the service life of the power transformer is ensured by a decrease in the intensity of thermal wear of the insulation of the most loaded winding.